2020
DOI: 10.3390/fib8120073
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation Treatment for the Batch Processing of Natural Fibers: Effects on Constituents, Tensile Properties and Surface Morphology of Selected Plant Stem Fibers

Abstract: This work was on the comparative evaluation of the property effects obtainable when acetylation is applied to parts of selected agro fibers that are obtainable within common localities. The fibers were subjected to different concentrations of acetylation treatment at ambient temperature for 3 h. The physico-chemical, morphological, and tensile properties of the fibers were examined after the treatment. It was discovered from the results that the procedures variedly influenced the constituents of the fibers, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 45 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Higher aspect ratio fibres are typically stiffer. Natural fibre aspect ratios vary significantly for a number of reasons [ 48 ]. The following Table 2 compares the aspect ratios of untreated and 0.1 M alkali treated Zm root fibres.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher aspect ratio fibres are typically stiffer. Natural fibre aspect ratios vary significantly for a number of reasons [ 48 ]. The following Table 2 compares the aspect ratios of untreated and 0.1 M alkali treated Zm root fibres.…”
Section: Resultsmentioning
confidence: 99%
“…Density is the primary factor considered while choosing plant fibres to replace synthetic ones. When selecting materials for various applications, weight is a significant criterion [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, natural fiber reinforced composites have essentially replaced synthetic fiber reinforced composites in a range of technical applications due to their low cost, high specific strength, biodegradability, renewability, and efficient thermal and acoustic insulating characteristics. [1][2][3][4][5] Natural fibers are derived from plant and animal bodies or from geological processes. [10 -13].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] For outstanding performance, chemical surface treatments have been employed to modify the structural constituents and surface morphology of natural fibers to enhance their compatibility with polymer matrix, reduce moisture absorption, and promote fiber/ matrix adhesion. In this regard, some reports have demonstrated that silanization, 9,10 acetylation, [10][11][12] benzoylation, and peroxide treatment 10,13,14 improve the surface properties of natural fibers for better application performance. Overall, silane treatment has been demonstrated to be better than some other surface treatment methods in improving the interfacial property of natural fibers.…”
Section: Introductionmentioning
confidence: 99%